PENENTUAN STRATEGI PEMASARAN BERAS HERBAL FORTE CV AN-NAHLAH JEMBER - Yudhistira, Novan (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2017)
Abstract:The purpose of this study was to identify the internal (strengths and weaknesses) and external (opportunities and threats) factors influencing the marketing of Forte Herbal Rice and to formulate alternative marketing strategies that can be used by CV. An Nahlahas the seller. The sampling method used was convenience sampling with a sample size of 32 (thirty two) respondents. The analysis tool used is the Strenghts Weaknesses Opportunities Threats (SWOT) analysis. Using external internal matrix approach, CV. An Nahlah should apply a growth strategy. The SWOT analysis resulted in 5(five) main marketing strategies, i.e., lowering product prices, increasing thepromotion activities, optimizing social media to support promotion, supplying products to the stores located near to consumers, maintaining the stock of the product for the emerging market. Keywords: Strengths, Weaknesses, Opportunities, Threats, Marketing Strategy.